Habitat Associations of Red Imported Fire Ants (Solenopsis invicta) and Introduced Populations of Pseudacteon spp. Phorid Flies - Gold, Roger E (Sociobiology, 2014)
Habitat selection is one of many aspects of red imported fire ants, Solenopsis invicta Buren, (RIFA) that has been intensively studied since their initial introduction in the United States. Concurrently, innumerable studies have attempted to identify effective chemical insecticides for RIFA control. More recently, several species of Pseudacteon spp. phorid flies (Diptera: Phoridae) have been intensively evaluated to determine their potential utility in biologica control of RIFA. These flies belong to a suite of natural enemies of RIFA in their native South American range, and have been selected for release in the United States as biological control agents against RIFA. It is hypothesized that phorid flies, through parasitism and suppression of RIFA foraging, will provide measureable RIFA population suppression as phorid ranges expand and fly densities increase. Relatively little scientific attention has been paid to habitat selection and partitioning by these flies in their introduced range(s) in the US. We assessed RIFA and phorid (Pseudacteon curvatus and Pseudacteon tricuspis) densities in four central Texas habitats. The habitat types selected represent a continuum of habitat diversity, micro-habitat availability, and plant heterogeneity. Within the habitat types studied, RIFA mound densitieswere significantly different, but foraging intensity was not significantly different in three of four habitat types. Population densities of P. curvatus were determined to be significantly higher in one habitat than all others. Alternatively, P. tricuspis densities followed a trend within the surveyed habitats that correlated with RIFA densities observed in this study. These data imply that the successful release, establishment, and range expansion of P. curvatus may require a greater degree of critical consideration regarding the ecologyof each system into which they are released, as opposed to P. tricuspis. These implications also suggest that the successful establishment of additional phorid species in the US should take into consideration the habitat matrix and habitat-based expansion corridors available to the flies.